Robotic-assisted versus laparoscopic surgery: outcomes from the first multicentre, randomised, patient-blinded controlled trial in radical prostatectomy (LAP-01) - Stolzenburg, Jens-Uwe; Holze, Sigrun; Neuhaus, Petra; Kyriazis, Iason; Do, Hoang Minh; Dietel, Anja; Truss, Michael C.; Grzella, Corinn I.; Teber, Dogu; Hohenfellner, Markus; Rabenalt, Robert; Albers, Peter; et al. (European urology, 2021)
Background - The LAP-01 trial was designed to address the lack of high-quality literature comparing robotic-assisted (RARP) and laparoscopic (LRP) radical prostatectomy. - Objective - To compare the functional and oncological outcomes between RARP and LRP at 3 mo of follow-up. - Design, setting, and participants - In this multicentre, randomised, patient-blinded controlled trial, patients referred for radical prostatectomy to four hospitals in Germany were randomly assigned (3:1) to undergo either RARP or LRP. - Outcome measurements and statistical analysis - The primary outcome was time to continence recovery at 3 mo based on the patient’s pad diary. Secondary outcomes included continence and potency as well as quality of life in addition to oncological outcomes for up to 3 yr of follow-up. Time to continence was analysed by log-rank test and depicted by the Kaplan-Meier method. Continuous measurements were analysed by means of linear mixed models. - Results and limitations - A total of 782 patients were randomised. The primary endpoint was evaluable in 718 patients (547 RARPs; full analysis set). At 3 mo, the difference in continence rates was 8.7% in favour of RARP (54% vs 46%, p =  0.027). RARP remained superior to LRP even after adjustment for the randomisation stratum nerve sparing and age >65 yr (hazard ratio = 1.40 [1.09-1.81], p =  0.008). A significant benefit in early potency recovery was also identified, while similar oncological and morbidity outcomes were documented. It is a limitation that the influence of different anastomotic techniques was not investigated in this study. - Conclusions - RARP resulted in significantly better continence recovery at 3 mo. - Patient summary - In this randomised trial, we looked at the outcomes following radical prostate surgery in a large German population. We conclude that patients undergoing robotic prostatectomy had better continence than those undergoing laparoscopic surgery when assessed at 3 mo following surgery. Age and the nerve-sparing technique further affected continence restoration.